Failure analysis of heat exchange tubes in hydrogenation unit. (November 2021) - Liu, Yan; Qu, Yanpeng; Chang, Feng; Li, Songling
Highlights: The leakage failure of the austenitic stainless steel tubes in a hydrogenation unit was investigated. The directly reason of the failure is pitting corrosion and stress corrosion cracking. Improper heat treatment of the austenitic stainless tubes and existence of corrosive substances results in the occurrence of the corrosion. Complex flowing conditions accelerate the corrosion. Abstract: The leakage failure of the austenitic stainless steel tubes in the hydrogenation unit of a petrochemical company was analyzed. The causes of the failure were investigated by visual examination, chemical compositions analysis of the tube, microscopic examination, metallographic examination and scale layer analysis. The results showed that the directly reason of the failure is pitting corrosion and stress corrosion cracking. We concluded that the improper heat treatment of the austenitic stainless tubes and existence of the corrosive substances including wet hydrogen sulfide and hydrogen chloride in the working medium, result in the occurrence of the corrosion, and the complex flowing conditions accelerate the corrosion process. Proposals were put forward in this paper.